Zoning, Returns to Scale, and the Value of Undeveloped Land - Brownstone, David; Vany, Arthur De (The Review of Economics and Statistics, 1991)
When land markets are incomplete, parcels can be scaled to make control compatible with use and to internalize externalities. The authors show that an arbitrage-proof equilibrium implies an increasing and strictly concave relationship between the value and size of land parcels. Undeveloped land sales in southern California strongly confirm the theoretical relationship. The authors find that zoning primarily restricts the conversion of land from agriculture to residential and industrial uses relative to the competitive equilibrium. The scale of land units is an effective private instrument for providing compatible land use even in the presence of strong zoning. Copyright 1991 by MIT Press.